2015
DOI: 10.3892/etm.2015.2470
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the role of catabolite control protein A in the metabolic regulation of Streptococcus suis serotype 2 using gene expression profile analysis

Abstract: Abstract.Catabolite control protein A (CcpA) serves a key function in the catabolism of Streptococcus suis serotype 2 (S. suis 2) by affecting the biological function and metabolic regulatory mechanisms of this bacterium. The aim of the present study was to identify variations in CcpA expression in S. suis 2 using gene expression profile analysis. Using sequencing and functional analysis, CcpA was demonstrated to play a regulatory role in the expression and regulation of virulence genes, carbon metabolism and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
(34 reference statements)
1
1
0
Order By: Relevance
“…These results have been verified by a further metabolomics study by our group (19). A comparison of the data from the two studies indicated that ccpA affected overall pathogenicity, metabolites and virulence through different pathways (9,19). The altered functions of various metabolic proteins, including peptidoglycan glycosyltransferase, enolase, sortase, GAPDH, 6-phosphogluconate dehydrogenase and glutamine synthetase may have affected the virulence of the bacteria, which was also reported by a previous study (20).…”
Section: Discussionsupporting
confidence: 75%
“…These results have been verified by a further metabolomics study by our group (19). A comparison of the data from the two studies indicated that ccpA affected overall pathogenicity, metabolites and virulence through different pathways (9,19). The altered functions of various metabolic proteins, including peptidoglycan glycosyltransferase, enolase, sortase, GAPDH, 6-phosphogluconate dehydrogenase and glutamine synthetase may have affected the virulence of the bacteria, which was also reported by a previous study (20).…”
Section: Discussionsupporting
confidence: 75%
“…To characterize the GO terms, including molecular functions, biological processes, cellular components, and functional pathways of DEGs, significantly enriched GO terms was analyzed by a hypergeometric test, based on “GO Term Finder” (Boyle et al, 2004; Lang et al, 2015). All the DEGs were mapped to the terms in KO (KEGG Orthology) identifier (Kanehisa et al, 2012; Zeng et al, 2013) using KOBAS 2.0 to identify which pathways the significant DEGs belonged to.…”
Section: Methodsmentioning
confidence: 99%
“…Their studies underlined an involvement of CcpA in sugar, amino acid, nucleic acid and fat metabolism as ccpA activity alters the concentration of certain metabolites [85,86]. A decrease in succinic, aspartic, and citric acid concentrations changed glucose availability and therefore, affected S. suis metabolism regulation [87].…”
Section: Catabolite Control Protein a (Ccpa)mentioning
confidence: 99%
“…HPr an important co-factor of this binding is phosphorylated by the protein HP0197 [95]. CcpA is involved in diverse metabolic pathways, the expression of virulence factors and certain enzymes such as the α-galactosidase [13,24,84,85,87]. In addition, it takes part in glycolysis and galactose utilization.…”
Section: Catabolite Control Protein a (Ccpa)mentioning
confidence: 99%